256 The effect of closely meeting estimated daily lysine and energy requirements of pregnant first parity sows on offspring growth and carcass quality. (30th November 2020) - Hansen, Lauren; Stewart, Victoria; Mandell, Ira; Huber, Lee-Anne
Abstract: A total of 141 pigs from 24 litters were used to determine the effects of closely meeting estimated lysine and energy requirements for first parity sows during gestation on subsequent offspring growth performance until slaughter and carcass and loin quality. Sows were assigned a control (static diet composition; CON) or precision (specialized daily blend of two diets to meet estimated nutrient and energy requirements; PF) feeding regimen between d7 and 110 of gestation (n=12). At weaning (21 days of age), six pigs per litter were randomly selected and placed in a pen (1 pen per litter). All pens received ad libitum access to commercial diets in 6 phases (4-phase nursery, grower, and finisher, respectively). Individual body weights and per pen feed intakes were recorded weekly (nursery and finishing phases) or biweekly (growing phase). Four pigs per pen were slaughtered at ~125kg BW to measure carcass and loin quality. During nursery phase-3, ADG (0.60 vs. 0.53±0.02 kg/d;P< 0.05) and G:F (0.88 vs. 0.79±0.02;P< 0.05) were greater for pigs from PF versus CON sows. The ADFI in nursery phase-4 tended to be greater for pigs from PF versus CON sows (1.9 vs. 1.2±0.06 kg/d; P=0.05). By day 66 of age (end of nursery phase), pigs from PF sows had greater BW than those from CON (31.8 vs. 30.0±0.5 kg; P< 0.05); no further differences were observed for growth performance. After slaughter, there were no differences in carcass quality (e.g., hot carcass weight and lean yield) but the loin color for pigs from PF sows tended to be darker (L*; 47.4 vs. 46.5±0.1; P=0.06) and less red (a*; 6.5 vs. 6.8±0.3P=0.09) than CON. Closely meeting daily requirements for first parity sows during gestation improved offspring growth in the nursery phase, while carcass and loin quality at ~125 kg BW were generally not affected.